A high glucose concentration is well tolerated by colorectal adenocarcinoma and melanoma cells but toxic to normal human gingival fibroblast: Results of an in vitro investigation - Mazlan, Muhammad Alif; Yusof, Afzan Mat; Md Isa, Muhammad Lokman (UI Scholars Hub, 2020)
Background: Glucose is associated with weight gain, which increases the risk of cancer. There is insufficient information on the effects of high glucose concentrations on cell lines. This study evaluated the viability patterns of human cancer and normal cell lines treated with glucose. Methods: Human gingival fibroblast (hGF), colorectal adenocarcinoma (HT29), and skin malignant melanoma (A375) cell lines were cultured and treated with additional glucose in three respective concentrations: 1 mg/ml, 5 mg/ml, and 10 mg/ml. Then, cell viability was measured using an MTT(3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide)-assay. The data were analyzed using the Statistical Package for the Social Sciences software. Results: The hGF cells’ percentage pattern of viability showed a rapid decline of nearly 95% on the third day of treatment. Both HT29 and A375 were able to survive in the high glucose condition when the cell viability percentage was above 100% on Day 5. The data exhibited significance; the p-value was less than 0.001. Conclusion: The high glucose concentration can be toxic to hGF. In addition, HT29 and A375 might be adaptive to the hyperglycaemic condition.